Anti-NDV activity of 9-oxo10, 11-dehydroageraphorone extracted from Eupatorium adenophorum Spreng in vitro. Issue 18 (17th September 2018) - Xu, Ruiguang; Weng, Jiahua; Hu, Liwen; Peng, Guangneng; Ren, Zhihua; Deng, Junliang; Jia, Yan; Wang, Chengmin; He, Hongxuan; Hu, Yanchun
Abstract: The purpose of this study was to investigate the anti-Newcastle disease virus (NDV) activities of 9-oxo-10, 11-dehydroageraphorone (euptox A) from Eupatorium adenophorum Spreng ( E. adenophorum ) in vitro . NDV infection of chicken embryo fibroblasts (CEFs) was performed. Cytotoxicities and antiviral activities of euptox A was assessed by the MTT method. The interaction of NDV with cell membrane protein was detected by virus overlay protein binding assay (VOPBA). The expression levels of NDV genes in CEFs was tested by RTFQ PCR. The results showed that the maximal safe concentrations of euptox A to CEFs was 10 μg/mL. Euptox A could directly neutralise NDV, inhibit the infectivity of NDV to CEFs and block intracellular NDV treat NDV infection. And euptox A brings competitiveness inhibition for NDV binding to its receptors and then prevent NDV infection. These results indicated that euptox A possessed anti-NDV activity has potential use as components of a natural antiviral drug. Abstract :